Sociohistorical Change in Urban Older Adults' Perceived Speed of Time and Time Pressure. (28th June 2021) - Löckenhoff, Corinna E; Drewelies, Johanna; Duezel, Sandra; Steinhagen-Thiessen, Elisabeth; Demuth, Ilja; Freund, Alexandra M; Staudinger, Ursula M; Lindenberger, Ulman; Wagner, Gert G; Ram, Nilam; Gerstorf, Denis
Abstract: Objectives: Perceptions of time are shaped by sociohistorical factors. Specifically, economic growth and modernization often engender a sense of acceleration. Research has primarily focused on one time perception dimension (perceived time pressure) in one subpopulation (working-age adults), but it is not clear whether historical changes extend to other dimensions (e.g., perceived speed of time) and other subpopulations, such as older adults who are no longer in the workforce and experience age-related shifts in time perception. We therefore examined sociohistorical and age-related trends in two dimensions of time perception in two cohorts of urban older adults. Method: Using propensity score matching for age and education, samples were drawn from the Berlin Aging Study (1990–1993, n = 256, M age = 77.49) and the Berlin Aging Study-II (2009–2014, n = 248, M age = 77.49). Cohort differences in means, variances, covariance, and correlates of perceived speed of time and time pressure were examined using multigroup SEM. Results: There were no cohort differences in the perceived speed of time, but later-born cohorts reported more time pressure than earlier-born cohorts. There were no significant age differences, but perceptions of speed of time were more heterogeneous in the 1990s than in the 2010s. Cohorts did not differ in how time perceptions were associated with sociodemographic, health, cognitive, and psychosocial correlates. Discussion: These findings document sociohistorical trends toward greater perceived time pressure and reduced heterogeneity in perceived speed of time among later-born urban adults. Conceptualizations of social acceleration should thus consider the whole adult life span.